Training on the Introduction of Python Applications in Mathematics Learning for Grade 7 Junior High School Students in Yogyakarta - Aulia Fonda; Katon Agung Ramadhan; Muh Wildanul Firdaus; Junianto; Indi Mega Aulia (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The government plans to introduce programming languages, commonly called coding. Students must be able to understand how to program an application and not only be a user but it is expected that students have the provision to develop the technology. The utilization of technology encourages humans to use it for the right things. The participatory method is carried out through four stages: focus group discussion (FGD), socialization, training, and evaluation. The subjects of this PKM are teachers and 7th-grade junior high school students in Yogyakarta. Grade 7 students are expected to start learning programming languages as early as possible. Using the Python application, students can learn programming for math learning. Math is often considered a difficult lesson; with this training, students become happy to explore. The training conducted can be used to learn the basics of Python and create formulas to calculate the area of flat buildings.